Determination to Survive in Anne Enright’s Novel the Green Road (2015) - Alvie Luthfiana Jeklor Putri; Desvalini Anwar (English Language and Literature, 2020)
The purpose of this analysis is to expose the issue of determination to survive in novel The Green Road (2015) by Anne Enright. The issue of determination to survive refers to how the protagonist whose name is Constance reacts and makes efforts in facing life hardships.  This analysis looks at the protagonist’s two effort done by the character which are building strong self-acceptance and being independent. This analysis is related to life instinct theory proposed by Sigmund Freud. The uses of the theory is based on the interpretation of the text and context of the novel. This analysis also depends a lot on fictional devices such as character, plot (conflict) and setting to determine which part of the novel that will be used as the data. The result of the study reveals that the protagonist builds her self-acceptance and shows her independence in order to survive.